Musculocartilaginous structure of the external ear in dromedary camels with special reference to auricular nerve blocks - Allouch, Gamal Mounir; Alshanbari, Fahad Abdullah; Sadan, Madeh (Frontiers in Veterinary Science, 2025)
AimUnderstanding the external ear’s anatomy and the ear nerve blocks (particularly in the external acoustic meatus) is crucial for facilitating effective ear movement and treating clinical cases requiring an ear nerve block. The purpose of this study was to describe the anatomical cartilages and muscular structures of the outer ear and to investigate the appropriate anatomical location of the major nerves supplying the ear in dromedary camels.MethodsThe study was conducted on 12 adult male and female dromedary camel heads of different breeds, obtained from the Buraydah slaughterhouse. The standard dissection technique was employed by placing the samples in a 10% formalin solution before dissecting them using approved dissection tools.ResultsThe findings demonstrated that the auricle of camels has a particular structure. The muscles were organized into four groups: rostral, dorsal, ventral, and caudal. In addition, three cartilages were identified, along with the anatomical location of the auricular nerves. Based on anatomical and ultrasonographic landmarks, the injection sites for the internal and great auricular nerve blocks were determined at the lateral side of the base of the auricular cartilage and at the base of the pinna on its caudal side, respectively.ConclusionThe study provides detailed information about the ear pinna, cartilages, and muscles of the camel, with a particular focus on the auricular nerve block method. These findings can serve as a guide future for clinical and surgical procedures involving the camel’s ear.